2020
DOI: 10.32604/fdmp.2020.010407
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of the TipWake of aWind Turbine Impeller Using Extended Proper Orthogonal Decomposition

Abstract: The behavior of the tip wake of a wind turbine is one of the hot issues in the wind power field. This problem can partially be tackled using Computational Fluid Dynamics (CFD). However, this approach lacks the ability to provide insights into the spatial structure of important high-order flows. Therefore, with the horizontal axis wind turbine as the main focus, in this work, firstly, we conduct CFD simulations of the wind turbine in order to obtain a data-driven basis relating to multiple working conditions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They also performed POD decomposition on the flow field and observed that the conditional average reveals more significant coherent structures at larger scales compared to the conventional ensemble average. Wu et al [37] conducted computational fluid dynamics (CFDs) simulations on a horizontal axis wind turbine and analyzed the data using an extended proper orthogonal decomposition (POD) algorithm. The quantitative findings suggest that the wake's tip vortex exhibits a complex spatiotemporal morphological configuration in the higher-order extended POD space, while also confirming the effectiveness and reliability of the obtained radial velocity modes.…”
Section: Introductionmentioning
confidence: 99%
“…They also performed POD decomposition on the flow field and observed that the conditional average reveals more significant coherent structures at larger scales compared to the conventional ensemble average. Wu et al [37] conducted computational fluid dynamics (CFDs) simulations on a horizontal axis wind turbine and analyzed the data using an extended proper orthogonal decomposition (POD) algorithm. The quantitative findings suggest that the wake's tip vortex exhibits a complex spatiotemporal morphological configuration in the higher-order extended POD space, while also confirming the effectiveness and reliability of the obtained radial velocity modes.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics is a new interdisciplinary subject that integrates fluid mechanics and computer science. It is applied in several fields such as medical care, aviation, and high-speed rail [17][18][19][20]. Currently, most numerical simulations of aircraft wake vortices are based on a simplified rectangular wing.…”
Section: Introductionmentioning
confidence: 99%
“…Reliability is the probability that the machine or equipment can work continuously without failure at the time specified in the expected operating conditions [11]. The effectiveness of these approaches is assessed by the reliability indicators (MTBF) [12], availability (MTTR) [13], the percentage of implementation of PM (Preventive maintenance) programs and the rate of emergency maintenance [14], defined in the strategic management process [15] as well as the quality of the maintenance activities. In the vibration measurement and analysis of the vibrations, with the goal of reducing emergency stops and increasing the reliability of very sensitive equipment, rotary machines, the CM (Condition Monitoring) approach is used [16].…”
Section: Introductionmentioning
confidence: 99%